1995
DOI: 10.1093/clinchem/41.6.867
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of antioxidant enzymes in sepsis: preliminary assessment

Abstract: The prognostic potential of the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) was evaluated in sepsis. Enzyme concentrations were determined in samples obtained from septic patients at time of diagnosis. Statistically significant increases in activities of total plasma SOD (P < 0.003, n = 32), erythrocyte (RBC) SOD (P < 0.007, n = 16), plasma CAT (P < 0.0001, n = 32), and RBC CAT (P < 0.005, n = 16) were found in septic patients when compared with healthy adult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…Warner et al showed that the plasma SOD concentration was elevated in septic patients, and levels were higher in non-survivors of sepsis compared to survivors [27]. Recently, we showed that lower erythrocyte SOD1 activity was an early predictor of the development of acute renal injury in patients with septic shock [8].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Warner et al showed that the plasma SOD concentration was elevated in septic patients, and levels were higher in non-survivors of sepsis compared to survivors [27]. Recently, we showed that lower erythrocyte SOD1 activity was an early predictor of the development of acute renal injury in patients with septic shock [8].…”
Section: Discussionmentioning
confidence: 69%
“…When total redox capacity is measured is sepsis, a clear decrease is seen in septic patients compared to healthy controls [25]. In addition, this redox capacity usually remains low in patients who die, whereas it returns to normal in patients who survive sepsis [25][26][27]. It is also important to observe that mitochondria are a major source of ROS, and at the same time, a target for oxidative damage [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference is expected because of the increased production of the superoxide ion and hydrogen peroxide in septic patients. Plasma SOD is high in non-survivors of sepsis but tends to decrease to about a third of these high levels in survivors [23] . When total redox capacity is measured in sepsis instead of individual free radicals or oxidized cell components, a clear decrease is seen in septic patients compared to healthy controls.…”
Section: Role Of Reactive Oxygen Species In Acute Diseasementioning
confidence: 94%